2019
DOI: 10.1007/s10681-019-2520-4
|View full text |Cite
|
Sign up to set email alerts
|

Can a speed breeding approach accelerate genetic gain in pigeonpea?

Abstract: Pure line breeding is a resource-intensive activity that takes 10 years or more to develop a new cultivar. In some crops, conducting off-season nurseries has significantly reduced the length of the breeding cycle. This approach could not be exploited in pigeonpea [Cajanus cajan (L.) Millsp.], because traditionally it has been a photoperiod-sensitive crop that requires long periods of darkness to induce flowering. However, the recent success of breeding early maturing photoperiod-insensitive genotypes has opene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…The use of speed breeding has been adapted to different conditions from fully enclosed growth chambers to greenhouses to facilitate single‐seed descent (SSD) systems in plant breeding programs (Ghosh et al., 2018). For instance, spring wheat, durum wheat ( Triticum durum L.) (Ghosh et al., 2018), barley, chickpea ( Cicer arietinum L.) (Ghosh et al., 2018), pea ( Pisum sativum L.) (Ghosh et al., 2018), pigeonpea ( Cajanus cajan L.) (Saxena, Saxena, Hickey, & Varshney, 2019), and orphan crops (Chiurugwi, Kemp, Powell, & Hickey, 2019) can be grown up to six consecutive generations per year via the speed breeding technique instead of two or three generations per year under normal greenhouse conditions. In oat, the use of speed breeding has shown a 15‐ to 20‐d average reduction in flowering time compared with the conventional system (Ghosh et al., 2018; Heuschele, Case, & Smith, 2019; Liu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The use of speed breeding has been adapted to different conditions from fully enclosed growth chambers to greenhouses to facilitate single‐seed descent (SSD) systems in plant breeding programs (Ghosh et al., 2018). For instance, spring wheat, durum wheat ( Triticum durum L.) (Ghosh et al., 2018), barley, chickpea ( Cicer arietinum L.) (Ghosh et al., 2018), pea ( Pisum sativum L.) (Ghosh et al., 2018), pigeonpea ( Cajanus cajan L.) (Saxena, Saxena, Hickey, & Varshney, 2019), and orphan crops (Chiurugwi, Kemp, Powell, & Hickey, 2019) can be grown up to six consecutive generations per year via the speed breeding technique instead of two or three generations per year under normal greenhouse conditions. In oat, the use of speed breeding has shown a 15‐ to 20‐d average reduction in flowering time compared with the conventional system (Ghosh et al., 2018; Heuschele, Case, & Smith, 2019; Liu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Applying the single seed descent (SSD) method under highly controlled growth conditions has reduced generation time in wheat and barley 2 . Harvesting and germination of the immature seeds, thereby shortening the generation cycle, have been proven for wheat, pigeon pea, and faba bean 2 , 34 , 35 . Hence, there is a potential for further reducing the generation cycle, at least by three to four weeks in our oilseed rape populations, by combining SSD with immature seed harvesting and germination under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated shortening of generation time by combining harvesting of immature seeds and single pod descent method. Another SB-based strategy by Saxena et al (2019) employed early maturating photoperiod-insensitive genotypes, and showed its potential to deliver new early maturing cultivars with the successful reduction of up to 4-5 years. SB recipes combined with single seed descent and MAS or GS will provide greater genetic gains over conventional methods of plant breeding (Varshney et al 2021).…”
Section: Rapid Generation Turnover (Rgt) Technologiesmentioning
confidence: 99%